He ara waiora / A pathway towards wellbeing. Exploring Te Ao Māori perspectives on the Living Standards Framework for the Tax Working Group - Emily O'Connell; Tia Greenaway; Trevor Moeke; Sacha McMeeking (New Zealand Government, The Treasury, 2018)
"Nāu te rourou, nāku te rourou, ka ora ai te iwi" - "With your contribution and mine, the people will prosper". The vision of the New Zealand Treasury is to promote higher living standards for all New Zealanders. The Treasury has always recognised that there are many possible ways to understand intergenerational wellbeing. The Treasury indicated earlier this year that the Crown-Māori relationship is integral to all four capitals in our Living Standards Framework (LSF), and that the Treasury would be further exploring how this might be reflected in the framework...
Keywords: 330